Penerapan Geogebra terhadap Kemampuan Pemecahan Masalah Matematis Siswa dalam Pembelajaran Matematika - Alfito Fatihah; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
Currently, many learning media are used to develop and improve students' mathematical abilities, especially students' problem-solving abilities. One of the learning media that can be used in this case is the Geogebra application. The purpose of this study is to provide a description of the application of geogebra to students' mathematical problem solving abilities in mathematics learning. This study adopted from the Systematic Literature Review Method and selected 15 articles from google scolar data that are relevant to the research focus. The results of the study concluded that the application of geogebra had a positive, effective, and superior impact in improving students' mathematical problem solving abilities in the learning process.